Study on the Length and the Breadths of Tendoachilles of Human Cadaver (Bangladesh Journal of Medical Science, 2018)
Background: Tendoachilles is the chief plantar flexor of the ankle joint. The present study was conducted to find out the possible variations of tendoachilles between the right and the left leg of both male and female.Materials and methods: A cross sectional observational study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from July 2013 to June 2014. The data were collected from both the right and the left tendoachilles of 60 human cadavers taken from Anatomy Departments of different Government and Nongovernment Medical Colleges in Dhaka city. Among the 60 cadavers, 30 were male and 30 were female. After dissection, the length of tendoachilles and the breadths at different levels of tendoachilles were measured and recorded.Results: The mean length of tendoachilles was significantly greater in the right than in the left leg of both male and female. The tendoachilles was longer in male than in female in both the right and the left leg (P0.05).Conclusion: Significantly greater values were observed in the length and in most of the breadths of tendoachilles in the right leg of both sexes and in male in both legs. There was significant positive correlation between the height of cadaver and the length of tendoachilles of both legs in case of male, but, not in female.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.388-394